2015
DOI: 10.1097/ta.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute care surgery on appendicitis outcomes

Abstract: Background Acute appendicitis is the most common indication for emergency general surgery (EGS) in the US. We examined the role of acute care surgery (ACS) on interventions and outcomes for acute appendicitis at a national sample of university-affiliated hospitals. Methods We surveyed senior surgeons responsible for EGS coverage at University HealthSystems Consortium (UHC) hospitals, representing >90% of university-affiliated hospitals in the US. The survey elicited data on resources allocated for EGS during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Clinician availability may reduce the oversight required for timely termination of perioperative antibiotics, in the absence of an established pathway, or advanced practice provider (APP) to help guide care. These aspects likely contributed to the low frequency of an enhanced recovery after surgery (ERAS) approach that includes same day discharge for uncomplicated appendicitis in otherwise healthy adults [45,46]. Nonetheless, our data demonstrate that practice can conform to guideline-based recommendations-which suggests the lack of an evidence-to-practice gap-across very different healthcare systems (USA, Estonia, Romania), at least in participating centers.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Clinician availability may reduce the oversight required for timely termination of perioperative antibiotics, in the absence of an established pathway, or advanced practice provider (APP) to help guide care. These aspects likely contributed to the low frequency of an enhanced recovery after surgery (ERAS) approach that includes same day discharge for uncomplicated appendicitis in otherwise healthy adults [45,46]. Nonetheless, our data demonstrate that practice can conform to guideline-based recommendations-which suggests the lack of an evidence-to-practice gap-across very different healthcare systems (USA, Estonia, Romania), at least in participating centers.…”
Section: Discussionmentioning
confidence: 79%
“…Clinician availability may reduce the oversight required for timely termination of perioperative antibiotics, in the absence of an established pathway, or advanced practice provider (APP) to help guide care. These aspects likely contributed to the low frequency of an enhanced recovery after surgery (ERAS) approach that includes same day discharge for uncomplicated appendicitis in otherwise healthy adults [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…69,70 This model,however has been viewed largely from the perspective of the proponets of the acute care paradigm as an isolated, hospital-based service line; but, our prior research suggests that the resource intensiveness of a round-the-clock acute care surgery service may not be practical at all hospitals, in particular, the smaller hospitals lacking a trauma center caable of providing 24/7 coverge. 71,72 Therefore, this paradigm of acute care surgery should be understood, by surgeon leaders, hospital administrators, and regional public health officials alike, as a network for patients presenting for EGS care centered around an EGS Center of Excellence (i.e., the hospitals with an acute care surgery service).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that while ACS implementation is increasing, uptake is uneven across regions. Yet early reports from hospitals adopting ACS suggest a number of improvements in quality, costs, and outcomes including optimal OR use, reduced length of stay, and improved mortality . Furthermore, regional studies indicate that patients with general surgery emergencies may have specific demographic, comorbid, and physiologic risk factors that warrant early referral to ACS hospitals with constant OR preparedness and specialized critical care resources .…”
Section: Discussionmentioning
confidence: 99%